Optimalisasi pemanfaatan limbah filter rokok sebagai outsole sandal melalui teknik vulkanisasi: Studi eksplorasi material - Adita, Sekar; Tembriano, Dommy (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
Cigarette filter waste is one of the most rapidly increasing types in many countries, including Indonesia. Composing this waste, composed of cellulose acetate, is a lengthy process that can result in considerable environmental contamination. This research aims to optimize the utilization of cigarette filter waste as an alternative material to replace sandal soles, which are typically manufactured from plastic or cellulose foam. The research encompasses the identification and collection of waste, its processing into a fine powder, the formulation development with a latex mixture, and the testing of the resulting material's strength and flexibility. The methodology employed is a material exploration study, whereby cigarette filter waste is processed by pressing techniques and combined with additional supporting materials to create a robust and flexible outsole. A series of physical and mechanical tests were conducted to assess the flexibility, strength, and water resistance of the material. The results demonstrated that the mixture of cigarette filter waste with latex adhesive yielded a sandal outsole that exhibited high strength, flexibility, water resistance, and environmental friendliness. The findings of this research indicate that the utilization of cigarette filter waste as a sandal outsole material not only mitigates environmental pollution but also provides an economical and sustainable alternative material.